2018
DOI: 10.1007/s12274-018-2243-1
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Schottky barrier width and enormously enhanced photoresponsivity in Sb doped SnS2 monolayer

Abstract: Doping, which is the intentional introduction of impurities into a material, can improve the metal-semiconductor interface by reducing Schottky barrier width. Here, we present high-quality two-dimensional SnS 2 nanosheets with well-controlled Sb doping concentration via direct vapor growth approach and following micromechanical cleavage process. X-ray photoelectron spectroscopy (XPS) measurement demonstrates that Sb contents of the doped samples are approximately 0.22%, 0.34% and 1.21%, respectively, and dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 55 publications
(38 reference statements)
1
52
0
Order By: Relevance
“…In brief, as V G is applied and electrons are injected from the Au S/D electrodes, cations are drawn from the electrolyte into the n‐type OSC . Electrons are subsequently transferred/donated from the ions to dope the OSC, shifting the Fermi level and reducing the height/width of the Schottky barrier, hence reducing R C . This results in similar R C at high V G , regardless of the initial R C magnitude.…”
Section: A Summary Of the Dispersive And Polar Surface Energy Componementioning
confidence: 99%
“…In brief, as V G is applied and electrons are injected from the Au S/D electrodes, cations are drawn from the electrolyte into the n‐type OSC . Electrons are subsequently transferred/donated from the ions to dope the OSC, shifting the Fermi level and reducing the height/width of the Schottky barrier, hence reducing R C . This results in similar R C at high V G , regardless of the initial R C magnitude.…”
Section: A Summary Of the Dispersive And Polar Surface Energy Componementioning
confidence: 99%
“…Similarly, in our previous work, we reported enhanced optical and electrical properties of SnS 2 nanoflakes via Cu doping [35]. More recently, Liu et al reported enhanced photoresponsivity in Sb doped SnS 2 monolayer [36]. Based on the above literatures we test the ability of doping Zn ions in SnS 2 to significantly enhance conductivity and sensitivity favorable for its performance in photoelectronics.…”
Section: Introductionmentioning
confidence: 63%
“…Last but not the least, Duan et al used their famous two-step CVD method to fabricate a Sb/WSe 2 heterostructure. The thickness of Sb nanosheet on WSe 2 can be effectively reduced to monolayer [45].…”
Section: Antimonymentioning
confidence: 99%
“…Nevertheless, because of the covalent bonding between the anion/ion atoms and the general weak interlayer coupling effect, TMCs and their heterostructures have suffered from intrinsic/extrinsic disorder (vacancies, anti-site, substitution) and interface impurity (small molecules), leading to the downtrend or strange phenomenon in electronic and optoelectronic properties [38,39]. Fortunately, the charge transport [40], photoluminescence [41], layer-dependent magnetism [42] and electrical properties [43][44][45][46] of TMCs can be enhanced via some specific kinds of defects (point substitution or deep levels). Among them, monoelement doping in 2DLMs has attracted researchers because of the unique properties of monoelements.…”
Section: Introductionmentioning
confidence: 99%